LO SVILUPPO MORALE E RELIGIOSO IN ADOLESCENZA. ASPETTI PSICOLOGICI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Moral and Religious Development during Adolescence. Psychological AspectsMoral and religious development represents a very complex argument, with many sides, that is why it can be studied from many points of view (philosophic, theological, psychological, sociologic etc.), and among the same approaches we can see different methods of analysis. The present article approaches the theme of moral and religious development during the period of adolescence, making reference both to the psychoanalytic theory, and to the theory of social and cognitive- behavioral learning. Thus, we will see that the religious and moral development do not have the same development rhythms, and their complementarity cannot be understood prior to the adolescence period. While the religious feeling can be already manifested as autonomous reality at a child, morality can be manifested autonomous only when there are the necessary premises for the values to be understood, shared, and manifested throughout a coherent behavior, being in a strong connection with cognitive development and with the way in which the person interacts with reality. In an ideal way, religiosity and morality should be integrated, and in this process of integration a very important role is being played by the parental education and the extra familial one.